Diversity and Nutritional Value of Local Vegetable Side Dishes (Pak Nhor) in Muang Khon–Style Thai Rice Noodle Meals within the Kao–Pa–Na–Lay Context of Nakhon Si Thammarat Province - Wongwichian, Chantira; Limsuwanmanee, Jutaporn; Khongtong, Jatuporn; Rodjaroen, Somrak (Wichcha Journal Nakhon Si Thammarat Rajabhat University, 2026)
This study aimed to investigate the diversity and nutritional value of processed local vegetable side dishes (Pak Nhor) served with Khanom Jeen in Nakhon Si Thammarat Province, within four geographical contexts: mountain (Kao), forest (Pa), rice field (Na), and coastal (Lay) areas. Data were collected through in-depth interviews with local knowledge holders and nutritional analyses of processed local vegetables. The results showed that processed Pak Nhor could be classified into three categories: sweet-and-sour pickled vegetables, coconut-blanched vegetables, and salad-type vegetables. Sweet-and-sour pickled vegetables and coconut-blanched vegetables were found in all areas, including pickled cucumber and pickled papaya. Salad-type vegetables were found only in the rice field (Na) area, including young mango salad and young mango salad with freshwater crab (Pu Piaw). In the mountain (Kao) area, pickled Luk Pra and pickled bitter bean (Sator) were found. The coastal (Lay) area featured pickled spider flower and a coconut-blanched mixed vegetable dish known as “Four Friends,” while the forest (Pa) area was characterized by Ajaad-style pickled cucumber and a coconut-blanched mixture of water spinach and banana stalk. Nutritional analysis indicated that different types of processed Pak Nhor had distinct nutrient compositions. Pickled nipa palm fruit, pickled banana pith, and pickled cucumber contained sugar levels of 15.09±0.04, 11.20±0.03, and 9.74±0.04 g per 100 g edible portion, respectively. In contrast, pickled Luk Pra, pickled Sator, and pickled spider flower contained high sodium levels of 1,256.70±0.57, 1,102.40±0.25, and 829.40±0.06 mg per 100 g edible portion, respectively. These findings highlight the potential of processed Pak Nhor as foods with biodiversity and nutritional value that can support local food consumption, community economic development, and the conservation of local culinary traditions.